Ranitidine – update on latest FDA actions - Basu, Debasis (International Journal of Basic & Clinical Pharmacology, 2026)
Ranitidine has maintained a key therapeutic role in managing acid-related disorders due to its favourable efficacy–tolerability profile and consistent pharmacodynamic behaviour. Since its introduction, clinicians have relied on its consistent and sustained suppression of gastric acid secretion, which has translated into effective relief of gastroesophageal reflux symptoms, improved healing of peptic ulcers, and dependable control of episodic acid-related discomfort. Decades of clinical use have generated a robust and reassuring evidence base demonstrating ranitidine’s safety and effectiveness across diverse patient populations.